Dynamic Spending Responses to Wealth Shocks: Evidence from Quasi-Lotteries on the Stock Market - Asger Lau Andersen; Niels Johannesen; Adam Sheridan (Center for Economic Studies and ifo Institute (CESifo), 2021)
How much and over what horizon do households adjust their consumption in response to stock market wealth shocks? We address these questions using granular data on spending and stock portfolios from a large bank and exploiting lottery-like variation in gains across investors with similar portfolio characteristics. Consistent with the permanent income hypothesis, spending responses to stock market gains are immediate and persistent. The responses cumulate to a marginal propensity to consume of around 4% over a one-year horizon. The estimates differ substantially by household liquidity, but not by financial attention, as measured by the frequency of account logins.
Keywords: 330; wealth shocks; household consumption; marginal propensity to consume; permanent income hypothesis